Cellular Distribution and Gene Expression Pattern of Metastasin (S100A4), Calgranulin A (S100A8), and Calgranulin B (S100A9) in Oral Lesions as Markers for Molecular Pathology. (2nd July 2016) - Reckenbeil, Jan; Kraus, Dominik; Probstmeier, Rainer; Allam, Jean-Pierre; Novak, Natalija; Frentzen, Matthias; Martini, Markus; Wenghoefer, Matthias; Winter, Jochen
ABSTRACT: The objective of this study was to analyze cellular localization and expression levels of oncologic relevant members of the S100 family in common oral lesions.Biopsies of various oral lesions were analyzed. S100A4 showed a higher expression rate in leukoplakias and oral squamous cell carcinomas. Transcript levels of S100A8 and S100A9 were significantly decreased in malignant OSCCs. A correlation could be drawn between the expression levels of these genes and the pathological characteristics of the investigated lesions. S100A4, A8, and A9 proteins represent promising marker genes to evaluate the risk potential of suspicious oral lesions in molecular pathology.